PNPLA7 mediates Parkin-mitochondrial recruitment in adipose tissue for mitophagy and inhibits browning - Xuetao Ji; Xu Zhang; Tong Zhang; Yao Xue; Mengping He; Chaopu Li; Yun Huang; Haoyu Wang; Jing Ju; Li’e Cai; Yuzhu Wang; Ning Wang; et al. (Nature Communications)
Abstract PINK1/Parkin-mediated ubiquitin-dependent mitophagy is a critical negative regulatory machinery for browning in the inguinal white adipose tissue (iWAT). However, the precise regulatory mechanism underlying PINK1/Parkin-mediated mitophagy during browning of iWAT remains largely unknown. Here we report that PNPLA7, an Endoplasmic Reticulum and mitochondria-associated membrane (MAM) protein, inhibits browning of iWAT by promoting PINK1/Parkin-mediated mitophagy upon cold challenge or β3-adrenergic receptor agonist treatment. With genetic manipulation in mice, we show that adipose tissue overexpressing PNPLA7 induces mitophagy, abolishes iWAT browning and interrupts adaptive thermogenesis. Conversely, conditional ablation of PNPLA7 in adipose tissue promotes browning of iWAT, resulting in enhanced adaptive thermogenesis. Mechanistically, PNPLA7 interacts with Parkin to promote mitochondrial recruitment of Parkin for mitophagy activation and mitochondria degradation by disrupting PKA-induced phosphorylation of Parkin under cold challenge. Taken together, our findings suggest that PNPLA7 is a critical regulator of mitophagy that resists cold-induced browning of iWAT, thus providing a direct mechanistic link between mitophagy and browning of iWAT.